Parameter Estimation Method For Fractional Order PNGV Battery Model - Balkış, Emre; Düven, Ekrem (My University, 2024)
Among the different types of batteries, Li-ion batteries are the most preferred type due to the performance and safety features they provide. Battery manage- ment systems are needed to get convenient performance from this kind of battery and to extend the life of batteries as much as possible. For this reason, an accurate battery model is required for a good battery management system. In this study, The Partnership for New Generation of Vehicles (PNGV) equivalent circuit battery model, which represents open circuit voltage changes, is taken as a basis and fractional order batteries models are created based on the PNGV equivalent circuit battery model. One of the most important subjects after creating the battery model is the determination of model parameters. At this stage, to make the problem simpler, the measured battery dataset is divided into sub-layers with a layered approach and the parameters are determined with analysis and data extractions on each sub-layer reflecting the different state of charge levels. This approach helped to obtain the accurate battery model with a steady state error of less than 5 mV and a transient error of less than 30 mV during each current pulse.
Keywords: Lithium-ion batteries; Battery parameter estimation; fractional order calculation; PNGV battery model.